Factors associated with Insomnia Severity Index among elderly participants - Panda, Manasi; Sandooja, Chirag; Kumar, Vinod; Kishore, Jugal (Indian Journal of Community Health, 2023)
Background: Amongst various psychiatric disorders in the elderly, insomnia is one of the major challenges. Aims & Objectives: To assess the prevalence of insomnia and the factors associated with it among the elderly. Material & Methods: This cross-sectional study was conducted in a rural and an urban area of Delhi taking 115 participants from each area using systematic random sampling. A semi-structured questionnaire was to collect the data. Results: Out of 230 participants, 121 (52.6%) were females and 109 (47.4 %) were males. Insomnia was more prevalent in the elderly participants of rural area (95%) while just 5% were in the urban population. Out of the 230 participants, 113 (49.1%) had scores of 0-7 whereas 117 (50.9%) had scores between 8-28 which meant they had some degree of insomnia. Insomnia was significantly associated with the locality of the participants (p-value <0.05). Conclusion: In the present study, around half of the elderly persons were suffering from Insomnia. As the cause of insomnia is multi-factorial, it needs a multi-pronged approach to prevention which can be achieved by creating awareness, management, and prevention. Further, screening elderly persons for insomnia and health education regarding the importance of sleep hygiene practices should be started.